2016
DOI: 10.1177/1559325816632102
|View full text |Cite
|
Sign up to set email alerts
|

Salt-Dependent Aggregation and Assembly of E coli-Expressed Ferritin

Abstract: Ferritin, with the primary function of iron storage, is a nearly ubiquitous protein found in most living organisms. Our recent investigations suggest that ferritin can assemble nanoparticles. So we use ferritin as a novel type of delivery vehicle for recombinant epitope vaccines. And, we found that ferritin form nonnative aggregates depended sensitively on NaCl concentrations. Here, we report that ferritin is an ion-sensitive protein and has the attribute of salt-dependent aggregation. Our results indicate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…It has been reported that ionic strength plays an important role in the stability and self-assembly of ferritins ( 53 , 54 ). We examined the effect of salt concentration on the formation and stability of the RBD-[SSG]-FR NPs at various concentrations (0–300 mM).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that ionic strength plays an important role in the stability and self-assembly of ferritins ( 53 , 54 ). We examined the effect of salt concentration on the formation and stability of the RBD-[SSG]-FR NPs at various concentrations (0–300 mM).…”
Section: Resultsmentioning
confidence: 99%
“…As intrinsic factors, the concentration of salts and Fe 2+ also influenced the assembly and stability of NPs (Figures 3 and 4 ). The ionic strength played an important role in the stability and self-assembly of ferritins, and aggregation increased with increasing concentrations of NaCl ( 54 ). The assembly of the hybrid MERS-CoV NPs revealed an interesting change in salt dependence, with 200–225 mM NaCl buffer as optimal condition as confirmed by EM and DLS analyses (Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To demonstrate tES rescue of GFPuv expression, GFPuv was induced at 0.8 (O.D. 600 nm) due to its extremely low expression in late exponential phase 10 . While leaving isopropyl β-D-1-thiogalactopyranoside (IPTG) concentration constant (0.4 mM), L-arabinose was varied from 0.001 to 0.1%.…”
Section: Resultsmentioning
confidence: 99%
“…1a ) 8 , 9 . Second, while eukaryotic ferritin assemblies are stable in low-salt concentrations 10 , AfFtn disassociates in low-salt (NaCl) concentrations 8 .
Fig.
…”
Section: Introductionmentioning
confidence: 99%